Chylomicronemia through a burr hole: A case report - Loh, Wann Jia; Bakthavachalam, Ramesh; Subramaniam, Tavintharan; Pek, Sharon; Chua, Fionn; Lee, Lester; Watts, Gerald F. (Frontiers in Cardiovascular Medicine, 2022)
Chylomicronemia has either a monogenic or multifactorial origin. Multifactorial chylomicronemia is the more common form and is due to the interaction of genetic predisposition and secondary factors such as obesity, diabetes, unhealthy diet, and medications. We report a case of a 38-year-old man who was diagnosed with multifactorial chylomicronemia following presentation with a subarachnoid hemorrhage requiring emergency surgery through a burr hole; lactescent cerebrospinal fluid mixed with blood was observed through the burr hole. The serum triglyceride concentration was 52⋅4 mmol/L with a detectable triglyceride concentration in the cerebrospinal fluid. Rapid weight gain leading to obesity and related unfavorable lifestyle factors were identified as key secondary causes of chylomicronemia. Gene testing revealed a homozygous variant in APOA5 and a heterozygous common variant in GPIHBP1. Accompanied with secondary causes, the interactions of gene and environmental conditions contribute to chylomicronemia. With aggressive medical treatment including excess weight loss, healthy diet, cessation of alcohol, and combination of anti-lipemic medications, normal plasma triglyceride levels were achieved.